ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT GENERASI MILENIAL DALAM MENGGUNAKAN KPR SYARIAH DI JABODETABEK - Fani Ramadhani (2021)
The enthusism of milennial generation in using financing product for Home Ownership Credit or Sharia mortgage has experienced significant developments from year to year. As with supply, availability, and housing sales in Jabodetabek have also increased. The purpose of this study is to determine the effect of accessibility (X1), economic factors (X2) and religious (X3) on the interest of the millennial generation in using housing loans or Sharia KPR in Jabodetabek (Y). The sample used in this study was 120 millennial generation in the Jabodetabek area. The instrument used in obtaining data was a questionnaire using a Likert scale then analyzed with the help of the IBM SPSS Statistics version 23 application program. The result of the study show that simultaneously accessibility, economics factor, and religious variables have a significant influence on the millennial generation's interest in using Sharia mortgages. Partially accessibility of the variable shows a negative but significant effect. Meanwhile, economic factors and religious variables have a positive and significant impact on millennial interest in using Sharia mortgages